Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
[tex]2 - \sqrt{-4} - 3 + \sqrt{-16} [/tex]
[tex]= 2 - i\sqrt{4} - 3 + i\sqrt{16} [/tex]
[tex]= 2 - 2i - 3 + 4i [/tex]
[tex]= -1 + 2i [/tex]
[tex]= 2 - i\sqrt{4} - 3 + i\sqrt{16} [/tex]
[tex]= 2 - 2i - 3 + 4i [/tex]
[tex]= -1 + 2i [/tex]
The square root of (-4) = square root of (-1) x (4) = 2i
The square root of (-16) = square root of (-1) x (16) = 4i
So now you have the sum of (2 - 2i) and (-3 + 4i).
The real part of the sum is (2 - 3) = -1
The imaginary part of the sum is ( -2i + 4i ) = +2i
The whole sum is -1 + 2i .
The square root of (-16) = square root of (-1) x (16) = 4i
So now you have the sum of (2 - 2i) and (-3 + 4i).
The real part of the sum is (2 - 3) = -1
The imaginary part of the sum is ( -2i + 4i ) = +2i
The whole sum is -1 + 2i .
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.